2012
DOI: 10.1371/journal.pone.0031040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization, Tissue Distribution, Subcellular Localization and Actin-Sequestering Function of a Thymosin Protein from Silkworm

Abstract: We identified a novel gene encoding a Bombyx mori thymosin (BmTHY) protein from a cDNA library of silkworm pupae, which has an open reading frame (ORF) of 399 bp encoding 132 amino acids. It was found by bioinformatics that BmTHY gene consisted of three exons and two introns and BmTHY was highly homologous to thymosin betas (Tβ). BmTHY has a conserved motif LKHTET with only one amino acid difference from LKKTET, which is involved in Tβ binding to actin. A His-tagged BmTHY fusion protein (rBmTHY) with a molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(47 reference statements)
0
9
2
Order By: Relevance
“…A Nikon Confocal Microscope and EZ‐C1 software were used to analyze the treated cells. Cy3‐labeled goat antirabbit IgG emitted red fluorescence when stimulated with light at 550 nm, and DAPI‐stained nuclei emitted blue fluorescence when stimulated with light at 353 nm (Zhang et al., ). The result showed that BmATAT1 is located in the cytoplasm and cell nucleus (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A Nikon Confocal Microscope and EZ‐C1 software were used to analyze the treated cells. Cy3‐labeled goat antirabbit IgG emitted red fluorescence when stimulated with light at 550 nm, and DAPI‐stained nuclei emitted blue fluorescence when stimulated with light at 353 nm (Zhang et al., ). The result showed that BmATAT1 is located in the cytoplasm and cell nucleus (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In bulls, TMSB10 protein was primarily detected in the head and tail area of testicular and ejaculated sperms, but the expression was limited to the equatorial segment of sperm during epididymal development (Howes et al, ). A homologous thymosin β protein in silkworm was highly expressed in the ovarian cells at the fifth‐instar larval period, however the expression of this protein was detected lower in the testis (Zhang et al, ). These studies suggested that the expression and functions of the thymosin family members varies slightly among species.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time fluorescence quantitative RT-PCR primers of B. mori 18s rRNA have been reported previously (Zhang et al, 2012). The primers and their annealing temperatures are listed in Table 1.…”
Section: Cloning and Real-time Fluorescence Quantitative Rt-pcr Primementioning
confidence: 99%